2015
DOI: 10.3390/en8042473
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Capacities of Distributed Generation and Energy Storage in a Small Autonomous Power System Considering Uncertainty in Renewables

Abstract: This paper explores real power generation planning, considering distributed generation resources and energy storage in a small standalone power system. On account of the Kyoto Protocol and Copenhagen Accord, wind and photovoltaic (PV) powers are considered as clean and renewable energies. In this study, a genetic algorithm (GA) was used to determine the optimal capacities of wind-turbine-generators, PV, diesel generators and energy storage in a small standalone power system. The investment costs (installation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Since the carbon dioxide emissions are relatively low (about 20 g/kWh) for the PV system [29] and even less for the wind turbine system, the carbon emissions of the proposed renewable energy generation system are neglected in this paper.…”
Section: Distributed Renewable Power Generation Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the carbon dioxide emissions are relatively low (about 20 g/kWh) for the PV system [29] and even less for the wind turbine system, the carbon emissions of the proposed renewable energy generation system are neglected in this paper.…”
Section: Distributed Renewable Power Generation Systemmentioning
confidence: 99%
“…where a, b, and c, the carbon emission coefficients, are respectively assigned the values of 28.144, 1.728, and 0.0017 in this paper [29].…”
Section: Distributed Diesel Generator Systemmentioning
confidence: 99%
“…In a power system, there is a great deal of uncertainty due to stochastic changes in the load, random unit outages and unpredictable faults in power lines [1,2]. When disturbances and faults occur, there could be fluctuations or drops in the frequency, and backup power resources that can respond instantly play a significant role in frequency maintenance and recovery.…”
Section: Introductionmentioning
confidence: 99%
“…[18]. In terms of the more complex energy systems, a co-optimization method was presented to determine the optimal operation strategy along with the optimal system configurations, indicating that the new structured CCHP system performs much better than the conventional separate system in the annual cost of the CCHP [19]. When taking the influence of the shortage of energy supplies into consideration, the results showed that the economy of the system would be improved if we design the system considering tolerance for energy supply shortages [20].…”
Section: Introductionmentioning
confidence: 99%